2022
DOI: 10.1186/s40001-022-00828-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of interstitial lung disease associated with primary Sjögren's syndrome

Abstract: Objectives The aim of this study was to investigate serum biomarkers linked to primary Sjögren's syndrome (pSS)-associated interstitial lung disease (ILD). Methods 69 pSS patients were consecutively enrolled and evaluated via quantitative ILD scoring based on high-resolution computed tomography (HRCT). Biomarkers of interest were assessed by multiplex enzyme-linked immunosorbent assays (ELISAs). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
12
2
Order By: Relevance
“…Eleven studies had a prospective design, and among them four were conducted in Greece [ 17 , 18 , 19 , 20 ], three in Sweden [ 21 , 22 , 23 ], one in Spain [ 24 ], one in the Netherlands [ 25 ], two in Italy [ 26 , 27 ], and one in China [ 28 ]. Nineteen studies had a retrospective design, and among them ten were conducted in China [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], three in Turkey [ 38 , 39 , 40 ], two in France [ 41 , 42 ], one in Italy [ 26 ], one in the Netherlands [ 43 ], one in Japan [ 44 ], one in Spain [ 45 ], and one in Germany [ 46 ]. Many of them referred to pSS patients fulfilling the revised criteria proposed by the American–European Consensus Group [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven studies had a prospective design, and among them four were conducted in Greece [ 17 , 18 , 19 , 20 ], three in Sweden [ 21 , 22 , 23 ], one in Spain [ 24 ], one in the Netherlands [ 25 ], two in Italy [ 26 , 27 ], and one in China [ 28 ]. Nineteen studies had a retrospective design, and among them ten were conducted in China [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], three in Turkey [ 38 , 39 , 40 ], two in France [ 41 , 42 ], one in Italy [ 26 ], one in the Netherlands [ 43 ], one in Japan [ 44 ], one in Spain [ 45 ], and one in Germany [ 46 ]. Many of them referred to pSS patients fulfilling the revised criteria proposed by the American–European Consensus Group [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many of them referred to pSS patients fulfilling the revised criteria proposed by the American–European Consensus Group [ 47 ]. In 23 studies out of the 30 included HRCT was performed to investigate lung involvement [ 19 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The main characteristics of the selected studies are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with SS can manifest significant BAL lymphocytosis, but this was not proven to be an early sign of severe lung fibrosis (70). Type II pneumocytes in patients with ILD produce a mucin-like glycoprotein called KL-6 (71). The serum level of KL-6 correlates significantly with ILD prognosis and disease severity as defined by HRCT and is considered a potentially useful diagnostic marker for detecting asymptomatic SS-ILD patients (71)(72)(73).…”
Section: Treatmentmentioning
confidence: 99%